High-dielectric-constant temperature-stable PTFE-based high-frequency copper-clad plate and preparation method thereof
By combining modified ceramic filler and ball milling technology, microwave ceramic powder/Polytetrafluoroethylene glue solution was prepared, which solved the problem of the dielectric constant of PTFE-based high-frequency copper clad plate changing with temperature, and achieved the effect of high dielectric constant and low-temperature drift coefficient.
Patent Information
- Application Number
- CN202411924073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The existing PTFE-based high-frequency copper clad plate with high dielectric constant has the problem that the dielectric constant changes with temperature, which leads to a change in the dielectric constant under the conditions of large changes in the use environment, affecting signal transmission.
By preparing modified ceramic fillers, combined with ball milling technology and dry modification technology, microwave ceramic powder/Polytetrafluoroethylene glue solution is prepared, which is used to prepare high dielectric constant temperature stable PTFE-based high-frequency copper clad plate.
The dielectric constant increase and temperature drift coefficient of PTFE-based high-frequency copper clad plate is achieved, and the temperature stability and signal transmission performance of the material are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminate preparation, and in particular to a high dielectric constant temperature-stable PTFE-based high-frequency copper clad laminate and a preparation method thereof. Background Art
[0002] With the rapid development of modern communication technology, miniaturization, high integration and high reliability have become the development direction of the new generation of communication equipment, which also puts forward requirements for high dielectric constant and low loss copper clad laminate materials. Polytetrafluoroethylene (PTFE) has the smallest dielectric loss, strong corrosion resistance and ultra-low water absorption, which is very suitable for manufacturing low loss copper clad laminate materials.
[0003] At present, a lot of work has been done on the research and industrial application of PTFE-based high-frequency copper-clad laminates at home and abroad, and outstanding industrial application results have been achieved. Rogers, AGC, Taizhou Wangling, Wuxi Ruilong Technology and other companies have successively put PTFE-based copper-clad laminates with high dielectric constants into the market as mature products. However, there is an obvious defect in PTFE-based high-frequency copper-clad laminates with high dielectric constants: their dielectric constant (DK) changes greatly with the change of operating temperature, especially at high frequencies, that is, the temperature drift coefficient (TCεr) of the dielectric constant is relatively large. For example: the TCεr of Rogers' AD1000 is about -380ppm / ℃, the TCεr of AGC's RF-10 is about -370ppm / ℃, the TCεr of Taizhou Wangling's F4BTMS1000 is about -320ppm / ℃, and the TCεr of Ruilong's RA1000 is about -368ppm / ℃. A larger temperature drift coefficient will cause the copper clad laminate material to have a larger DK change when the ambient temperature changes greatly, resulting in a phase difference, which in turn affects signal transmission. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art. The present invention proposes a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate and a preparation method thereof, and prepares a PTFE-based high-frequency copper-clad laminate product with a high dielectric constant and a low temperature drift coefficient.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate, comprising the following steps:
[0006] S1. preparing a microwave ceramic powder / polytetrafluoroethylene glue solution, wherein the glue solution includes a modified ceramic filler and polytetrafluoroethylene dissolved in a solvent, and the weight ratio of the modified ceramic filler to the polytetrafluoroethylene is 60-90:10-40;
[0007] S2, dipping the desized electronic-grade glass fiber cloth into the glue solution obtained in S1 for multiple times and drying and sintering to obtain a dipped film;
[0008] S3, cutting the obtained dipped film, covering both sides with electrolytic copper foil and hot pressing to obtain a high-frequency copper clad laminate;
[0009] The preparation method of the modified ceramic filler comprises the following steps:
[0010] a. Mixing a variety of ceramic powder raw materials by mechanical ball milling, grinding the obtained mixture, sintering by solid phase reaction, and then ball milling to crush the powder particle size to D50 to obtain a mixed powder;
[0011] b. spraying the obtained mixed powder with the modified solution, drying and crushing the mixed powder to obtain the modified ceramic filler;
[0012] The pH value of the modified solution is 3-4. The modified solution includes ethanol and amino-hydrocarbon-based silane coupling agent. The weight ratio of the amino-hydrocarbon-based silane coupling agent to ethanol is 1:1.5.
[0013] Furthermore, the preparation process of the mixed powder comprises the following steps:
[0014] a1. Mix various ceramic powder raw materials together by mechanical ball milling, with a ball milling speed of 400-450rpm / min and a ball milling time of 1-10h;
[0015] a2. Transfer the resulting mixture into a stainless steel barrel and dry it in an oven at 100°C for more than 1 day. Grind the blocky ceramic filler into fine powder using a mortar;
[0016] a3. Place the mixed ceramic filler into a high-temperature muffle furnace, calcining at a temperature of 800-1400°C, a calcining time of 0.5-10h, and a heating and cooling rate of 4-20°C / min;
[0017] a4. The sintered ceramic filler is subjected to mechanical ball milling treatment, with a ball milling speed of 400-450rpm / min and a ball milling time of 0.5-2h. The particle size of the ball milled powder is (D50) 1-10μm and the specific surface area is 0.8-4m 2 / g.
[0018] Further, the ceramic powder raw material includes at least two of CaCO3, Li2CO3, Nd2O3, Sm2O3, Na2CO3, TiO2, SiO2, and Bi2O3, and the ratio of the ceramic powder raw materials is CaCO3: Li2CO3: Nd2O3: Sm2O3: Na2CO3: TiO2: SiO2: Bi2O3 = 5-10: 5-20: 10-50: 40-70: 5-10: 20-50: 20-30: 75-90. For example, when preparing ceramic fillers, when the ceramic powder raw materials selected are Li2CO3, Sm2O3 and Na2CO3, their mass ratio is Li2CO3: Sm2O3: Na2CO3 = 5-20: 40-70: 5-10. When the corresponding amount of ceramic powder raw materials is selected for use in the preparation process of ceramic fillers, the proportioning is carried out according to the ratio between the aforementioned ceramic powder raw materials.
[0019] Furthermore, the modification process of the mixed powder comprises the following steps:
[0020] b1. Add the mixed powder into a high-speed kneader, spray the modified solution onto the powder during low-speed stirring, and then accelerate the stirring to complete the mixing;
[0021] b2. Take out the modified powder particles, dry them, crush them manually and pass them through a 325-mesh sieve to obtain surface-modified microwave dielectric ceramic powder.
[0022] Furthermore, the microwave ceramic powder / polytetrafluoroethylene glue specifically comprises the following steps:
[0023] S11, add 100 parts by weight of deionized water into a beaker, adjust the pH value to 3-4 with formic acid while stirring at a low speed, then add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker, and stir until clear;
[0024] S12, transferring the obtained solution to a high-speed stirrer and adding the modified ceramic filler, and dispersing at high speed for 60 minutes to obtain a ceramic filler slurry;
[0025] S13. Transfer the ceramic filler slurry to a low-speed mixer and stir at a low speed until the temperature drops below 40°C. Add a certain amount of polytetrafluoroethylene emulsion and stir at a low speed. During the stirring process, add 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type non-ionic surfactant; stir for 60 minutes to obtain the final glue solution, then stop stirring, and place the obtained glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation, which is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0026] Furthermore, the microwave ceramic powder / polytetrafluoroethylene glue solution also includes any one of strontium titanate or titanium dioxide, and the strontium titanate or titanium dioxide is added to the solution together with the modified ceramic filler, and the weight ratio of the ceramic filler, strontium titanate or titanium dioxide and polytetrafluoroethylene is 55-68:10-15:22-30.
[0027] Furthermore, in S2, the electronic grade glass fiber cloth is baked at 350°C for 5-10 minutes to complete the desizing treatment.
[0028] Furthermore, the glass fiber cloth impregnated with the adhesive solution is dried at 100° C. for 10 minutes and then sintered at 400° C. for 5 minutes to obtain a primary impregnated film, and then the impregnation with adhesive solution and the drying and sintering processes are repeated to obtain multiple impregnated films.
[0029] Furthermore, a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate is prepared according to a preparation method of a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate.
[0030] Compared with the prior art, the beneficial effects of the present invention include: first preparing ceramic fillers through a solid-phase sintering reaction combined with ball milling technology, then dry-modifying the prepared ceramic fillers to increase their affinity with PTFE resin, and finally applying them to the preparation process of high-dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminates. The prepared PTFE-based high-frequency copper-clad laminates have a higher dielectric constant and a satisfactory temperature drift coefficient. DETAILED DESCRIPTION
[0031] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific implementation modes are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.
[0032] A method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate comprises the following steps:
[0033] A: Preparation of microwave dielectric ceramic fillers;
[0034] B: Surface modification of the obtained powder;
[0035] C: Preparation steps of microwave ceramic powder / polytetrafluoroethylene copper clad laminate.
[0036] The preparation process of the aforementioned microwave dielectric ceramic filler comprises the following steps:
[0037] (1) Various ceramic powder raw materials are mixed together by mechanical ball milling, with a ball milling speed of 400-450 rpm / min and a ball milling time of 1-10 h.
[0038] (2) Then, the slurry was transferred to a stainless steel bucket and placed in an oven at 100°C to dry for more than 1 day. The blocky ceramic filler was ground into fine powder using a mortar.
[0039] (3) placing the mixed ceramic filler into a high-temperature muffle furnace, calcining at a temperature of 800-1400°C, a calcining time of 0.5-10h, and a heating and cooling rate of 4-20°C / min.
[0040] (4) The sintered ceramic filler is subjected to mechanical ball milling at a ball milling speed of 400-450 rpm / min and a ball milling time of 0.5-2 h. The particle size (D50) of the ball milled powder is 1-10 μm and the specific surface area is 0.8-4 m 2 / g.
[0041] The preparation of ceramic fillers is described below with reference to examples.
[0042] Preparation of ceramic filler 1
[0043] (1) Weigh 10 parts of Li2CO3, 40 parts of Nd2O3, and 45 parts of TiO2 and add them into a ball mill. Use ethanol as solvent and zirconium oxide balls as ball milling media. Mill for 6-10 hours in a planetary ball mill at a speed of 400 rpm / min.
[0044] (2) Then, the slurry was transferred to a stainless steel bucket and placed in an oven at 100°C to dry for more than 1 day. The blocky ceramic filler was ground into fine powder using a mortar.
[0045] (3) Then, the evenly mixed fine powder is spread in a corundum crucible and placed in a high-temperature muffle furnace. The temperature is raised to 1000°C at a rate of 10-20°C / min in an air atmosphere, kept at this temperature for 2 hours, and the heating is stopped to allow the furnace to cool naturally.
[0046] (4) Grinding the sintered powder obtained in step (3) to obtain coarse particles, and then placing 300-400 g of the coarse particles into a 1L zirconia ball mill using zirconia balls as the medium, and grinding them using a laboratory small ball mill to obtain dielectric ceramic filler fine powder. The speed of the ball mill is controlled at 400 rpm / min, and the ball milling time is controlled at 0.5-2 h.
[0047] Preparation of ceramic filler 2
[0048] (1) Weigh 6 parts of Li2CO3, 50 parts of Sm2O3, 8 parts of Na2CO3, and 24 parts of TiO2 and add them into a ball mill. Use acetone as solvent and zirconia balls as milling media. Mill in a planetary ball mill for 4 h at a speed of 400 rpm / °C.
[0049] (2) Then, the slurry was transferred to a stainless steel bucket and placed in an oven at 100°C to dry for more than 1 day. The blocky ceramic filler was ground into fine powder using a mortar.
[0050] (3) Then, the mixed fine powder is spread in a corundum crucible and placed in a high-temperature muffle furnace. The temperature is raised to 1300°C at a rate of 10-20°C / min in an air atmosphere and kept at this temperature for 2 hours. Then, the heating is stopped and the furnace is allowed to cool naturally.
[0051] (4) Grinding the sintered powder obtained in step (3) to obtain coarse particles, and then placing 300-400 g of the coarse particles into a 1L zirconia ball mill using zirconia balls as the medium, and grinding them using a laboratory small ball mill to obtain dielectric ceramic filler fine powder. The speed of the ball mill is controlled at 400 rpm / min, and the ball milling time is controlled at 0.5-2 h.
[0052] Preparation of ceramic filler 3
[0053] (1) Weigh 80 parts of Bi2O3 and 18 parts of Nd2O3 and add them into a ball mill jar. Use acetone as solvent and zirconium oxide balls as ball milling media. Mill for 4 hours in a planetary ball mill at a speed of 400 rpm / °C.
[0054] (2) Then, the slurry was transferred to a stainless steel bucket and placed in an oven at 100°C to dry for more than 1 day. The blocky ceramic filler was ground into fine powder using a mortar.
[0055] (3) Then, the uniformly mixed fine powder was spread in a corundum crucible and placed in a high-temperature muffle furnace. It was first calcined at 700°C for 5 h to allow Bi2O3 and Nd2O3 to react initially, and then kept at 930°C for 3 h. The muffle furnace was heated and cooled at a rate of 10-20°C / min. The heating was then stopped and the furnace was allowed to cool naturally.
[0056] (4) Grinding the sintered powder obtained in step (3) to obtain coarse particles, and then placing 300-400 g of the coarse particles into a 1L zirconia ball mill using zirconia balls as the medium, and grinding them using a laboratory small ball mill to obtain dielectric ceramic filler fine powder. The speed of the ball mill is controlled at 400 rpm / min, and the ball milling time is controlled at 0.5-2 h.
[0057] Preparation of ceramic filler 4
[0058] (1) Weigh 9 parts of CaCO3, 55 parts of Sm2O3, and 27 parts of SiO2 and add them into a ball mill. Use deionized water as solvent and zirconia balls as milling media. Mill in a planetary ball mill for 6-10 hours at a speed of 400 rpm / °C.
[0059] (2) Then, the slurry was transferred to a stainless steel bucket and placed in an oven at 100°C for drying for more than 3 days. The blocky ceramic filler was ground into fine powder using a mortar.
[0060] (3) Then, the uniformly mixed fine powder is spread in a corundum crucible and placed in a high-temperature muffle furnace. The temperature is raised to 950-1150°C at a rate of 10-20°C / min in an air atmosphere, and the temperature is kept at this temperature for 1-3 hours. Then, the heating is stopped and the furnace is allowed to cool naturally.
[0061] The sintered powder obtained in step (3) is ground to obtain coarse particles, and then 300-400 g of the coarse particles are placed in a 1L zirconium oxide ball mill using zirconium oxide balls as the medium, and ground using a laboratory small ball mill to obtain dielectric ceramic filler fine powder. The speed of the ball mill is controlled at 400 rpm / min, and the ball milling time is controlled at 0.5-2h.
[0062] The obtained dielectric ceramic filler fine powder is subjected to dry modification, which specifically comprises the following steps:
[0063] (1) Add 10g of amino hydrocarbon-based silane coupling agent into a sprayable plastic bottle, dilute with 1:1.5 ethanol, adjust the pH value to 3-4 with formic acid, and set aside.
[0064] (2) Add 500 g of powder into a small laboratory high-speed kneader. During low-speed stirring, spray the silane coupling agent / ethanol solution prepared in step (1) onto the powder in the kneader. After spraying, increase the stirring speed and stir for 15 minutes to complete mixing.
[0065] (3) Take out the modified powder particles and dry them directly in the air; or dry them in an oven at 120°C. After drying, crush them manually and pass them through a 325-mesh sieve to obtain surface-modified microwave dielectric ceramic powder.
[0066] The prepared ceramic fillers 1, 2, 3 and 4 are used to prepare microwave ceramic powder / polytetrafluoroethylene copper-clad laminates.
[0067] Comparative Example 1
[0068] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0069] (2) The solution was transferred to a high-speed mixer, and a certain amount of titanium dioxide was added. The mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, stirred at low speed, and when the temperature dropped below 40°C, a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The ratio of titanium dioxide to polytetrafluoroethylene was 68.1:31.9.
[0070] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0071] (4) Bake the electronic grade glass fiber cloth in an oven at 350°C for 5-10 minutes for desizing.
[0072] (5) Use deionized water to adjust the viscosity of microwave ceramic powder / polytetrafluoroethylene glue to ~100 CPS.
[0073] (6) The desized electronic grade glass fiber cloth is impregnated with microwave ceramic powder / polytetrafluoroethylene glue having adjusted viscosity.
[0074] (7) The glass fiber cloth impregnated with the adhesive solution is dried at 100°C for 10 min, and then sintered in a high-temperature oven at 400°C for 5 min to obtain a primary impregnated adhesive sheet.
[0075] (8) Repeat steps 6 and 7 for the once-impregnated film multiple times to obtain a multiple-impregnated film.
[0076] (9) The multi-impregnated film is cut into the required size, neatly stacked, and covered with 0.5OZ electrolytic copper foil on the upper and lower surfaces, and then placed between two steel plates, and hot-pressed by a vacuum hot press to obtain the high-frequency copper-clad laminate of the present invention. The hot-pressing conditions are temperature 370° C., pressure 1000 PSI, and time 100 min.
[0077] Example 1
[0078] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0079] (2) The solution was transferred to a high-speed mixer, and a certain amount of modified ceramic filler 1 was added, and the mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, and stirred at low speed until the temperature dropped below 40°C, and a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The ratio of modified ceramic filler 1 to polytetrafluoroethylene was 75:25.
[0080] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0081] (4) Bake the electronic grade glass fiber cloth in an oven at 350°C for 5-10 minutes for desizing.
[0082] (5) Use deionized water to adjust the viscosity of microwave ceramic powder / polytetrafluoroethylene glue to ~100 CPS.
[0083] (6) The desized electronic grade glass fiber cloth is impregnated with microwave ceramic powder / polytetrafluoroethylene glue having adjusted viscosity.
[0084] (7) The glass fiber cloth impregnated with the adhesive solution is dried at 100°C for 10 min, and then sintered in a high-temperature oven at 400°C for 5 min to obtain a primary impregnated adhesive sheet.
[0085] (8) Repeat steps 6 and 7 for the once-impregnated film multiple times to obtain a multiple-impregnated film.
[0086] (9) The multi-impregnated film is cut into the required size, neatly stacked, and covered with 0.5OZ electrolytic copper foil on the upper and lower surfaces, and then placed between two steel plates, and hot-pressed by a vacuum hot press to obtain the high-frequency copper-clad laminate of the present invention. The hot-pressing conditions are temperature 370° C., pressure 1000 PSI, and time 100 min.
[0087] Example 2
[0088] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0089] (2) The solution was transferred to a high-speed mixer, and a certain amount of modified ceramic filler 2 was added, and the mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, and stirred at low speed until the temperature dropped below 40°C, and a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The ratio of modified ceramic filler 2 to polytetrafluoroethylene was 70:30.
[0090] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0091] (4) Repeat steps (4) to (9) of Example 1 to obtain a high-frequency copper-clad laminate material.
[0092] Example 3
[0093] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0094] (2) The solution was transferred to a high-speed mixer, and a certain amount of modified ceramic filler 3 was added, and the mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, and stirred at low speed until the temperature dropped below 40°C, and a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The ratio of modified ceramic filler 3 to polytetrafluoroethylene was 65:35.
[0095] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0096] (4) Repeat steps (4) to (9) of Example 1 to obtain a high-frequency copper-clad laminate material.
[0097] Example 4
[0098] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0099] (2) The solution was transferred to a high-speed mixer, and a certain amount of modified ceramic filler 4 was added, and the mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, and stirred at low speed until the temperature dropped below 40°C, and a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The ratio of modified ceramic filler 4 to polytetrafluoroethylene was 85:15.
[0100] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0101] (4) Repeat steps (4) to (9) of Example 1 to obtain a high-frequency copper-clad laminate material.
[0102] Example 5
[0103] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0104] (2) The solution was transferred to a high-speed mixer, and a certain amount of modified ceramic filler 4 and strontium titanate were added, and the mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, and stirred at low speed until the temperature dropped below 40°C, and a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The mass ratio of modified ceramic filler 4, strontium titanate, and polytetrafluoroethylene was 55:15:30.
[0105] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0106] (4) Repeat steps (4) to (9) of Example 1 to obtain a high-frequency copper-clad laminate material.
[0107] Example 6
[0108] (1) Add 100 parts by weight of deionized water into a beaker, and adjust the pH value to 3-4 with formic acid while stirring at a low speed. Then, add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker and stir until it becomes clear.
[0109] (2) The solution was transferred to a high-speed mixer, and a certain amount of modified ceramic filler 4 and titanium dioxide were added, and the mixture was dispersed at high speed for 60 minutes to obtain a ceramic filler slurry. The ceramic filler slurry was transferred to a low-speed mixer, and stirred at low speed until the temperature dropped below 40°C, and a certain amount of polytetrafluoroethylene emulsion was added and stirred at low speed. The ratio of modified ceramic filler 4, titanium dioxide, and polytetrafluoroethylene was 68:10:22.
[0110] (3) During the stirring process, 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type nonionic surfactant is added to adjust the viscosity of the emulsion, improve the stability of the emulsion, and enhance the wetting performance of the emulsion. Stir for 60 minutes to finally obtain a glue solution. Stop stirring and place the glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation. This is the microwave ceramic powder / polytetrafluoroethylene glue solution.
[0111] (4) Repeat steps (4) to (9) of Example 1 to obtain a high-frequency copper-clad laminate material.
[0112] The basic properties of the PTFE-based high-frequency copper-clad laminates prepared in Comparative Example 1 and Examples 1-6 are shown in the following table:
[0113] Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Glue content (%) 92.87 93.93 94.88 94.15 94.25 93.22 93.78 DK(10Ghz) 9.3225 10.45 9.53 11.58 9.5885 8.825 10.30 DF(10Ghz) 0.00332 0.0044 0.0045 0.0041 0.00374 0.0035 0.0034 TCEr(ppm / ℃) -265.22 -53.48 -65.20 -50.77 10.4 -134.72 -154.41
[0114] As shown in the table above, in Examples 1-4, the obtained ceramic filler is directly mixed with polytetrafluoroethylene to obtain an emulsion and then applied to the subsequent high-frequency copper-clad laminate production process. Compared with the high-frequency copper-clad laminate obtained by directly applying titanium dioxide and polytetrafluoroethylene to the emulsion compound in Comparative Example 1, the dielectric constant (DK) is significantly improved, and the temperature drift coefficient (TCεr) of the dielectric constant of the obtained high-frequency copper-clad laminate is significantly smaller than the temperature drift coefficient (TCεr) of the dielectric constant of the high-frequency copper-clad laminate obtained in Comparative Example 1; in Examples 5-6, the obtained ceramic filler is directly mixed with polytetrafluoroethylene to obtain an emulsion and then applied to the subsequent high-frequency copper-clad laminate production process. After the material is mixed with strontium titanate or titanium dioxide and polytetrafluoroethylene to obtain an emulsion, it is applied to the subsequent production process of high-frequency copper clad laminates. Compared with Comparative Example 1, the temperature drift coefficient (TCεr) of the dielectric constant of the obtained high-frequency copper clad laminate is also significantly reduced, and compared with Examples 1-4, the temperature drift coefficient (TCεr) of the dielectric constant is significantly improved. Therefore, the prepared ceramic filler is directly compounded with polytetrafluoroethylene to obtain an emulsion and applied to the production process of high-frequency copper clad laminates, which has obvious advantages in dielectric constant (DK) and temperature drift coefficient (TCεr) of dielectric constant.
[0115] The technical scope of the present invention is not limited to the contents in the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate, characterized in that: The steps include: S1. preparing a microwave ceramic powder / polytetrafluoroethylene glue solution, wherein the glue solution includes a modified ceramic filler and polytetrafluoroethylene dispersed in a solvent, and the weight ratio of the modified ceramic filler to the polytetrafluoroethylene is 65-85:15-35; S2, dipping the desized electronic-grade glass fiber cloth into the glue solution obtained in S1 for multiple times and drying and sintering to obtain a dipped film; S3, cutting the obtained dipped film, covering both sides with electrolytic copper foil and hot pressing to obtain a high-frequency copper clad laminate; The preparation method of the modified ceramic filler comprises the following steps: a. Mixing a variety of ceramic powder raw materials by mechanical ball milling, grinding the obtained mixture, sintering by solid phase reaction, and then ball milling to crush the powder particle size to D50 to obtain a mixed powder; b. spraying the obtained mixed powder with the modified solution, drying and crushing the mixed powder to obtain the modified ceramic filler; The pH value of the modified solution is 3-4. The modified solution includes ethanol and amino-hydrocarbon-based silane coupling agent. The weight ratio of the amino-hydrocarbon-based silane coupling agent to ethanol is 1:1.
5.
2. The method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 1, wherein: The preparation process of the mixed powder comprises the following steps: a1. Mix various ceramic powder raw materials together by mechanical ball milling, with a ball milling speed of 400-450rpm / min and a ball milling time of 1-10h; a2. Transfer the resulting mixture into a stainless steel barrel and dry it in an oven at 100°C for more than 1 day. Grind the blocky ceramic filler into fine powder using a mortar; a3. Place the mixed ceramic filler into a high-temperature muffle furnace, calcining at a temperature of 800-1400°C, a calcining time of 0.5-10h, and a heating and cooling rate of 4-20°C / min; a4. The sintered ceramic filler is subjected to mechanical ball milling treatment, with a ball milling speed of 400-450rpm / min and a ball milling time of 0.5-2h. The particle size of the ball milled powder is (D50) 1-10μm and the specific surface area is 0.8-4m 2 / g.
3. The method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 2, wherein: The ceramic powder raw material includes at least two of CaCO3, Li2CO3, Nd2O3, Sm2O3, Na2CO3, TiO2, SiO2, and Bi2O3.
4. The method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 1, wherein: The modification process of the mixed powder comprises the following steps: b1. Add the mixed powder into a high-speed kneader, spray the modified solution onto the powder during low-speed stirring, and then accelerate the stirring to complete the mixing; b2. Take out the modified powder particles, dry them, crush them manually and pass them through a 325-mesh sieve to obtain surface-modified microwave dielectric ceramic powder.
5. The method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 1, wherein: The microwave ceramic powder / polytetrafluoroethylene glue solution specifically comprises the following steps: S11, add 100 parts by weight of deionized water into a beaker, adjust the pH value to 3-4 with formic acid while stirring at a low speed, then add 9 parts by weight of a propylene glycol polyether type nonionic surfactant into the beaker, and stir until clear; S12, transferring the obtained solution to a high-speed stirrer and adding the modified ceramic filler, and dispersing at high speed for 60 minutes to obtain a ceramic filler slurry; S13. Transfer the ceramic filler slurry to a low-speed mixer and stir at a low speed until the temperature drops below 40°C. Add a certain amount of polytetrafluoroethylene emulsion and stir at a low speed. During the stirring process, add 18 parts by weight of a branched secondary alcohol polyoxyethylene ether type non-ionic surfactant; stir for 60 minutes to obtain the final glue solution, then stop stirring, and place the obtained glue solution in an environment of 25°C for 48 hours. The glue solution remains stable without stratification or precipitation, which is the microwave ceramic powder / polytetrafluoroethylene glue solution.
6. The method for preparing the high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 5, characterized in that: The microwave ceramic powder / polytetrafluoroethylene glue solution also includes any one of strontium titanate or titanium dioxide. The strontium titanate or titanium dioxide is added to the solution together with the modified ceramic filler. The weight ratio of the ceramic filler, strontium titanate or titanium dioxide and polytetrafluoroethylene is 55-68:10-15:22-30.
7. The method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 1, characterized in that: In S2, the electronic grade glass fiber cloth is baked at 350°C for 5-10 minutes to complete the desizing treatment.
8. The method for preparing the high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 7, characterized in that: The glass fiber cloth impregnated with the adhesive is dried at 100°C for 10 minutes and then sintered at 400°C for 5 minutes to obtain a primary impregnated film, and then the impregnation with adhesive and the drying and sintering processes are repeated to obtain multiple impregnated films.
9. The method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate according to claim 1, characterized in that: During the hot pressing process, the temperature was 370° C., the pressure was 1000 PSI, and the time was 100 min.
10. A high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate, characterized in that: The laminate is prepared according to the method for preparing a high dielectric constant temperature-stable PTFE-based high-frequency copper-clad laminate as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Microwave dielectric ceramics and polytetrafluoroethylene-ceramic composite substrate, and preparation methods thereof
CN107746272A
Microwave dielectric ceramic powder filled fluororesin middle medium layer and preparation method thereof
CN108358505A
High frequency polytetrafluoroethylene copper clad plate and preparation method thereof
CN108822455A
Preparation method of composite laminate with high dielectric constant
CN109760384A
High-frequency copper-clad plate with low temperature drift coefficient and high dielectric constant and preparation method thereof
CN117241479A